Curculio tragiae F. - a baridine weevil collected by the Cook-Expedition in Brazil 1768 (Coleoptera: Curculionidae: Baridinae). - Prena, Jens (Contributions to Entomology = Beiträge zur Entomologie, 2005)
The history and origin of the type material of Curculio tragiae F. are reconstructed based on information in the description and historical evidence. The species is placed in the Baridinae as Nanobaris tragiae (F.) comb. n., where it takes priority over N. setosella (Hustache) syn. n. The original definition of Nanobaris Champion is modified to allow for the addition of species with elongate, spindle-shaped antennal club.Keywordsweevils, historical explorations, James Cook, Joseph Banks, Brazil.Nomenclatural Actssetosella Hustache, 1951 (Giveniopsis), syn. n. of Nanobaris tragiae (Fabricius, 1775)tragiae (Fabricius, 1775) (Nanobaris), comb. n. hitherto Curculio tragiae